Propuesta de un marco de trabajo metodológico de desarrollo de software para la Dirección de Tecnologías de Información de la Universidad Nacional de Loja. - Álvarez Pacheco, Máximo Andrés (2023)
The present Degree Work (DW) consists of proposing a methodological framework of software development in the Information Technologies Direction of the Universidad Nacional de Loja ITD-UNL, the analysis is started based on the adaptation process of agile methodologies of software development, framework and approaches more relevant currently, since to develop software is fundamental that work team selects the methodology or adjusts to one or several methodologies to the organizational reality, in this process it must be considered the size of the project, the organization, time and other resources. Thus, the present DW carries out an analysis of the current situation, that is to say: the stages, methodologies, devices and tools, which are used by those involved in the process of developing software in the ITD, after the agile methodologies of software development are analyzed and framework that focuses on delivering value to the customer in the shortest possible time, with the aim of identifying the roles, process, deliverable and best practices that will be common to each other and they could be used in the proposal, once the data is collected the methodological proposal is showed, with those components that increase the quality and productivity of team that participates on software development process of the ITD. The methodology called “qualitative research” was used in the development of this DW, because it is a scientific method of observation, its set of techniques allowed to get an overview of the problem, to generate ideas and/or assumptions and finally to identify and to pose the specific solutions. The main result by following this methodology is the proposal of the methodological framework, in which roles, lifecycles, practices, devices and tools are identified according to the organizational reality of the ITD, in such a way that the application of the proposal allows to standardize and to speed up the process of software development. Keywords: Agile methodologies, KANBAN, LEAN, SCRUM, Software project management, XP.